Microplastic Content in Water and Fish Species in Simanindo Waters, Lake Toba, North Sumatera: Microplastic Content in Water and Fish Species in Simanindo Waters, Lake Toba, North Sumatera - Siregar, Regita; Yusni , Eri; Sabrina, Tengku (Talenta Publisher, 2025)
With the activities in the waters of Lake Toba will affect the condition of the aquatic environment and also contribute to the presence of microplastics. One of the interesting waste problems in waters to discuss is the presence of microplastics in waters. Microplastics are certainly more than <5 mm in size, there are three processes of microplastic formation, namely biologically, chemically and physically. Microplastics can contaminate fish through fish organs such as gills and digestive tracts. The purpose of this study was to determine the form and abundance of microplastics in the respiratory tract and digestive tract of fish. This study was conducted from November to December 2024. The average abundance in water samples was 21-57 particles / gram while in digestive tract samples it was 37-42 particles / gr dry weight and the last respiratory tract sample was 9 159 particles / gr dry weight. The forms of microplastics found were film-shaped microplastics, fiber microplastics, fragment microplastics and pellet microplastics